2009
DOI: 10.1021/cr9001098
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Heterocyclic Synthesis

Abstract: Clarissa P. Frizzo was born in Ivora ´, Rio Grande do Sul state, Brazil, in 1983. She received her undergraduate degree in Pharmacy from the Federal University of Santa Maria in 2005, and in 2007 she obtained her M.Sc. degree from the Federal University of Santa Maria, under the supervision of Professor Marcos A. P. Martins, working with the use of ionic liquids in the synthesis of heterocycles. She started her Ph.D. studies under the supervision of Professor Marcos A. P. Martins, and currently she is focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
217
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 595 publications
(220 citation statements)
references
References 615 publications
1
217
0
2
Order By: Relevance
“…[1][2][3] Transformations of neat reactants under solvent-free reaction conditions (SFRC) are one of the best solutions in this regard. [4][5][6][7] In the solid/solid system, a remarkable reaction rate enhancement was observed just by introducing small amounts of solvent vapor into the reaction mixture. 8 Moreover, the course of the reaction can be dramatically influenced under highly concentrated reaction conditions (HCRC).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Transformations of neat reactants under solvent-free reaction conditions (SFRC) are one of the best solutions in this regard. [4][5][6][7] In the solid/solid system, a remarkable reaction rate enhancement was observed just by introducing small amounts of solvent vapor into the reaction mixture. 8 Moreover, the course of the reaction can be dramatically influenced under highly concentrated reaction conditions (HCRC).…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin a bicyclic ring characterized under benzo-alfa-pyrones which are abundantly found in nature. The structure of coumarin posses a wide pharmacological application which mainly found in anti-coagulant RESEARCH ARTICLE (warfarin), treating high protein edema in combination with troxerutin, immunomodlater in chronic infection, anti-cancer, antimalarial, antimicrobial, antibacterial, antifungal, antineurodegenerative, anti-oxidative, antiviral, antiparasitic, anti-inflammatory analgesic, antidiabetic, anti-depressive so on [5][6][7] . Schiff's base are also called imine derivatives which are formed by nucleophilic attack of aryl amine on electrophilic group of aldehyde or ketone in liberation of water called azomethine [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…17 We have used β-alkoxyvinyl trihalomethyl ketones (enones) to build five-, six-, and sevenmembered trihalomethylated heterocyclic compounds. [18][19][20][21] Also, our research group is continuously interested in a more environmentally benign synthesis, demonstrated by our recent papers that focus on solvent-free synthesis 22 and the use of ionic liquids as reaction media, 23 something that is associated with efficient techniques such as microwave 20,21 and ultrasound irradiation. 24 Due to our sustained interest in the study of heterocyclic synthesis and the lack of cyclocondensation reactions under pressurized CO 2 in the literature, herein, we wish to report a mild and efficient method for the preparation of NH-and phenyl-pyrazoles under pressurized CO 2 conditions.…”
Section: Introductionmentioning
confidence: 99%